De huid van de sculptuur. - Cotteleer, Anton (Antwerpen : Koninklijke Academie voor Schone Kunsten, 2018)
Van Dijck, Bart ; Cielen, Fie ; de Jong, Folkert ; Ervinck, Nick ; Buggenhout, Peter ; Rogiers, Peter ;Breukers, Tim ; Cotteleer, Anton
boek